Factors Influencing Substance Abuse/Dependence and Treatment Outcome of Adolescents in a Residential Substance Abuse Program: An Exploratory Study - Moody, Melissa L. (2003)
Previous research examining the risk factors associated with alcohol and other drug use has primarily focused on the adult population. Few studies have investigated the factors which influence adolescent substance abuse and the respective effects on treatment outcome. This in spite of the considerable decline in the age-of-onset for problematic substance use that could, if gone untreated, escalate into dependence and a variety of other interpersonal problems which extend across the lifespan. Effective interventions targeting the adolescent population would therefore seem to be of utmost importance to both researchers and clinicians. It has been suggested that individualized treatment programs focusing on the unique risk factors and needs of each client are paramount to the achievement of favorable treatment outcomes. Previous studies have focused on school populations and community samples with an emphasis on prevention and early intervention. The present study sought to examine the characteristics related to treatment outcome with a small sample of adolescents who had been admitted to a residential substance abuse program in rural Illinois to delineate the relationship between factors such as length of time in treatment, involvement with the judicial system, referral source, comorbid psychological problems and treatment outcome/retention. Significant differences were found between those adolescent clients who completed the program successfully and those who were unsuccessfully discharged or left against staff advice based on length of time spent in treatment. However, anticipated relationships between referral source, involvement with the legal system, comorbid psychiatric diagnoses and discharge status were not substantiated. Suggestions for future research are discussed